BUSINESS STRATEGY AND IMPLEMENTATION IN BINA SISWA - Poltak Pardamean Simarmata; Hengki Mangiring P Simarmata; Sudrajati Ratnaningtyas (Jurnal Ekonomi dan Bisnis (EK&BI), 2019)
Bina Siswa is a non-formal Tutoring service for primary school, junior high school and senior high school. Its address is at Belitung street number 22 Bandung. It was founded in May 2013, which previously was just a private course. The high learning interest of the students in Bandung gives positive impact to Bina Siswa institution, so every month Bina siswa always earns profit from this education business. After running for three years, the revenue of this business was relatively similar year by year, which is approximately IDR 20 million to 25 million every month. Because of that, the writer proposes a business strategy planning and implementation. By using PEST analysis, Porter's five forces, and competitor analysis, it’s known that Bina Siswa has several threats and opportunities of the external business environment. In internal analysis Bina Siswa use value chain analysis and existing business model canvas it’s known that Bina Siswa has Strengths and weakness. The results of the internal analysis and external analysis are used to build Strategy Formulation consists of Company Strategic and Functional Strategy. The best alternative proposed to Bina Siswa is growth strategy which concentrates in horizontal growth. The functional strategy of the company is developed by TOWS matrix, and implemented in several functional divisions. The implementation is formulated in short term strategy, medium term strategy, and long term strategy. This strategy planning is also included with schedules, action plans, budgeting, and the appointment of person in charge (PIC).